Multi-hop scatternet formation and routing for large scale Bluetooth networks. (27th July 2009) - Song, Wen-Zhan; Wang, Yu; Ren, Chao; Wu, Changhua, Xiang-Yang Li
This paper addresses the scatternet formation for large scale multi-hop Bluetooth networks. We first describe an efficient method to build a Connected Dominating Set (CDS) as the backbone of multi-hop Bluetooth network, then propose new algorithms to form the dBBlue scatternets (Song et al., 2005) in each cluster. The final scatternet, M-dBBlue, guarantees the connectivity. Our experiment shows our scatternet seldom parks any node. We then propose a complete set of hierarchical routing methods for M-dBBlue which enables the self-routing inside each cluster. Moreover, our scatternet formation and routing algorithm do not necessarily require position information of the node.